Kebutuhan Klien dan Caregiver, Kualitas Perawatan, Desain Program dan Peran Tenaga Kesehatan sebagai Penentu Keberhasilan Penerapan Total Care di Komunitas - Prastyanto, FX Bobby Tyas; Wiarsih, Wiwin; Permatasari, Henny; Setiawan, Agus (FORIKES, 2025)
Home or community health care is increasingly popular, driven by increasing life expectancy and the rise in chronic diseases. Total care is a multidisciplinary approach that encompasses physical, psychological, social, and spiritual aspects. The success of total care implementation depends on meeting the needs of clients and their satisfaction with the services. The purpose of this study was to determine the factors that influence client and family satisfaction in the implementation of total care in the community. This systematic review followed the PRISMA guidelines, with a literature search in ProQuest, ScienceDirect, Scopus, and PubMed. The keywords used were